Clinical trials as a factor affecting treatment results - Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2004)
The author is analyzing factors that according to him affect the treatment results. Apart from a generally accepted impact of the delayed treatment commencement and the lengthened diagnostic process he is analyzing other factors such as bias in clinical trials, publishing false data obtained during experimental studies and low percentage of the patients who receive optimal treatment. The actual results may be affected to a large extent by ethical and organizational transgressions of the researcher. Most frequent ethical transgressions include: not publishing results that are unfavorable for the researcher, comparing new pharmaceuticals with obsolete ones, negative evaluation of competitive products that is not supported with direct comparative studies. Most frequent errors of the researcher include: performing the research in the manner not matching the patient’s interests and overly frequent diagnostic examinations, which often brings about the risk of additional complications and overstating the overall health condition. Errors made by physicians themselves have a significant impact on the results of oncological treatment. Errors made during surgical therapy do not depend on funds, as in radiotherapy or chemotherapy, but to a greater extent on physicians’ qualifications. The paper also discusses the influence on alternative treatment on the quality of patient care in Poland.